The Geometrical Characterizations of the Bertrand Curves of the Null Curves in Semi-Euclidean 4-Space - Jianguo Sun; Yanping Zhao (Mathematics, 2021)
According to the Frenet equations of the null curves in semi-Euclidean 4-space, the existence conditions and the geometrical characterizations of the Bertrand curves of the null curves are given in this paper. The examples and the graphs of the Bertrand pairs with two different conditions are also given in order to supplement the conclusion of this paper more intuitively.